Enhancing Invoice Number Retrieval in Influencer Agency Transaction Records Using TF-IDF and SVC Model - Frisca Fitria (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This research explore the need for efficient invoice management in influencer marketing. The proposed solution using TF-IDF and SVC Model to effectively locate and handle crucial transaction information, including dates, brand names, invoice numbers, amounts, frequency and category. By using this approach to significantly improve the accuracy of identifying invoice numbers in influencer agency records. For the result this method are evaluated using precision accuracy and F1 Score metrics, to emphasize its effectiveness in current challenges of manual extraction. Overall, this paper offers practical solution to enhanced influencer agency transactions